"3D" Parametric and Nonparametric Description of Surface Topography in Manufacturing Processes - Królczyk, Grzegorz; Kacalak, Wojciech; Wieczorowski, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In present book, an analysis of the literature pertaining to parametric and non-parametric descriptions of surface topography in basics manufacturing processes (e.g., turning, milling, grinding) has been performed. The book focuses on the improvement of machining processes, with particular attention to the functional properties of surfaces, and, also, in the control of process parameters by a selected group of parameters. Here, the specific areas of interest are: surface topography analysis; advanced manufacturing metrology; surface metrology; measurement science; and measurement systems. The proposed approach of the description of surface for the functional properties of surfaces leads to the control of the whole manufacturing process, reduction of production cost by eliminating manufacturing defects and energy consumption, as well as the improvements of surface quality. The study presented in the book is a compendium of knowledge regarding surface metrology and emerging aim in a novel scientific approach.